Computer Graphics and Imaging - Sobota, Branislav (IntechOpen, 2019)
Computer graphics development is so quick that it has expanded from devices designed for military and top industrial applications to equipment for schools and households as common information media for education and entertainment. Computer graphics helps to mass expand computers and remove the barriers that ordinary people experience when working with them. In this book, modern approaches, procedures, algorithms, as well as devices in the area of light and colors, shading and lighting, realistic and photorealistic imaging, definition of graphical scenes or objects, and security based on graphical objects are presented. Graphical transformations and projections, spatial imaging, curves and surfaces, filling and texturing, image filtering, and virtual reality are also covered.